Propos sur la rationalisation de l’entreprise - Outreville, J.-François; Proulx, Carol; Thiboutot, Mario; P., G.; L., D. (Assurances, 1986)
In this article, Mr. Outreville studies certain aspects of rationalization, following the merger of enterprises in the province of Quebec. At the same time, he provides an abundant documentation on the subject, principally originating from American sources. For their part, Messrs. G.P. and D.L. present a specific case of rationalization at the administrative level from a holding, gathering different insurance, reinsurance and actuarial enterprises. The two papers appeared complementary to us, even though they have been conceived from different perspectives.